Thermal–hydraulic–mechanical–chemical coupled processes and their numerical simulation: a comprehensive review - Zhang, Nanlin; Luo, Zhifeng; Chen, Zhangxin; Liu, Fushen; Liu, Pingli; Chen, Weiyu; Wu, Lin; Zhao, Liqiang (Acta geotechnica, 2023)
With the growing development and utilization of underground space and resources, rock masses exposed to high stresses and pore pressure, large temperature changes, and complex hydraulic–chemical environments have become a research topic of wide interest. Such coupled physical and chemical processes strongly impact the rock mass’s mechanical properties and structural failure. Analyzing and studying rock’s mechanical properties and damage under multi-physics coupled environment can help ensure the safety and efficiency of exploiting underground mineral resources and developing underground space. Thermal–hydraulic–mechanical–chemical (THMC) coupled processes in rock masses have become a hot research topic, and the related numerical and experimental methods have made significant progress. This paper comprehensively reviews and evaluates the latest research progress on THMC coupling models and numerical methods. Finally, we summarize the key points, difficulties, and future THMC multi-physics coupling research directions and provide references for influencing mechanisms research and engineering practice.